2013
DOI: 10.4103/0972-124x.107473
|View full text |Cite
|
Sign up to set email alerts
|

Salivary protein concentration, flow rate, buffer capacity and pH estimation: A comparative study among young and elderly subjects, both normal and with gingivitis and periodontitis

Abstract: Background:To evaluate the salivary protein concentration in gingivitis and periodontitis patients and compare the parameters like salivary total protein, salivary albumin, salivary flow rate, pH, buffer capacity and flow rate in both young and elderly patients with simple methods.Materials and Methods:One hundred and twenty subjects were grouped based on their age as young and elderly. Each group was subgrouped (20 subjects) as controls, gingivitis and periodontitis. Unstimulated whole saliva was collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
55
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 14 publications
9
55
2
2
Order By: Relevance
“…The higher concentrations of hydrogen ions (from salivary glands or oral microbiota), the lowest the pH, since pH level negatively correlated with proportion of periodontal pathogens, that grow in mildly acidic pH, either utilize or create products that are mild to moderately acidic in nature (29) . The decrease in salivary FR in this study coincide with others concerning CP (15,19,29) , and DM (12,24,25,40) but diverge with previous studies about CP (37) and DM (41) who reported increased of FR, on the other hand some researchers found that FR levels not affected by periodontal health status (28) or presence of DM (42) . There are multiple causes of salivary hypofunction including inflammation e.g.…”
Section: Discussioncontrasting
confidence: 45%
“…The higher concentrations of hydrogen ions (from salivary glands or oral microbiota), the lowest the pH, since pH level negatively correlated with proportion of periodontal pathogens, that grow in mildly acidic pH, either utilize or create products that are mild to moderately acidic in nature (29) . The decrease in salivary FR in this study coincide with others concerning CP (15,19,29) , and DM (12,24,25,40) but diverge with previous studies about CP (37) and DM (41) who reported increased of FR, on the other hand some researchers found that FR levels not affected by periodontal health status (28) or presence of DM (42) . There are multiple causes of salivary hypofunction including inflammation e.g.…”
Section: Discussioncontrasting
confidence: 45%
“…21 Age may also have an effect on BC; in one study, BC was found to be higher among the elderly. 22 However, no significant differences in pH and BC were noted among individuals with different stages of periodontal disease. 22 In the current study, ALP activity levels were significantly lower in the smoker group than the control group, which may indicate the effect of smoking on salivary enzymes.…”
Section: Discussionmentioning
confidence: 91%
“…22 However, no significant differences in pH and BC were noted among individuals with different stages of periodontal disease. 22 In the current study, ALP activity levels were significantly lower in the smoker group than the control group, which may indicate the effect of smoking on salivary enzymes. The lower ALP levels observed among smokers may be explained by hyperkeratinisation of the oral and gingival mucosa, which could prevent the release of ALP in the saliva.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As said by Edgar 7 in his research that the rate of unstimulated salivary flow which increased from an average 0.3 ml / min up to 7 ml / min with stimulasi.Dawes 11 reported in his study that the average rate of unstimulated salivary flow 0.3-0.4 ml / min which if the salivary flow <0.1 ml / min prove any signs of hypo salivation. Shaila et al, 12 suggested that in addition to the factors of salivary flow that can affect an increase in total protein in saliva, there are several other factors that can affect, such as the contribution of the salivary gland proteins and protein sulcus fluid.…”
Section: Discussionmentioning
confidence: 99%